Heatwave adaptation for women farmers: Building resilience in the field - Macwan, N.; Maheriya, B.; Kori, Pooja; Verma, Benu; Puskur, Ranjitha (CGIAR GENDER Impact Platform, 2024)
Rising temperatures and extreme heat events pose severe risks to agricultural communities, particularly for women farmers who face unique vulnerabilities due to their roles in farming and households. Access to reliable and practical heat stress management information is crucial to ensuring their health, productivity, and overall resilience. To address this challenge, the Evidence Module of the CGIAR GENDER Impact Platform, led by the International Rice Research Institute (IRRI) in partnership with Mahila Housing Trust (MHT), has developed and tested a series of IEC materials, including two posters and one leaflet, to provide actionable guidance on mitigating heat stress. Through creative visuals these materials aim to enhance understanding, making complex climate information more accessible and relatable to women farmers. These resources highlight key adaptation strategies for rural areas such as staying hydrated, wearing protective clothing, modifying work schedules, and utilizing shaded rest areas. In addition, they also provide information on innovative solutions like heat-resilient farming techniques, water-efficient irrigation, and the use of early warning systems. By integrating these gender-responsive approaches, the IEC materials aim to enhance awareness and equip women farmers with the knowledge and tools necessary to adapt to increasing heat stress and safeguard their lives and livelihoods.